Pattern of parasitism in the carambola fruit fly, Bactrocera sp.(Malaysian A)(Dipt., Tephritidae) by Biosteres vandenboschi (Fullaway)(Hym., Braconidae) - Tock, Hing Chua (Blackwell Publishing Ltd, 1993)
Studies with carambolas collected from the field indicated that the mean number of of B. vandenboschi emerging from a larval patch (indicated externally by an ovipuncture) and from a whole fruit was respectively 5.02 ± 0.51 and 20.14 ± 1.93. In both cases, parasitism by B. vandenboschi was found to be inverse density dependent, with the respective equations of y = 97.99 e-0.12x and y = 32.54 e-0.03x where y = parasitism rate and x = total adult insects emerging from each fruit piece or a whole fruit. Likely reason for the inverse density dependent parasitism is the “spreading the risk” strategy employed by the female B. vandenboschi.